Power Relations In Changing the Culture Of The Community Power Relations In Changing The Culture Of Society - Ismail, Nawari (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
This study focuses on the workings of power between actors of unequal political and religious. The study used a qualitative approach with an ethnographic design. The study was conducted in a local religious community in the province of Central Java. The results are as follows: In the structure and relationships of unequal political and religious, power is practiced in a variety of social scopes through the fabric of social relations. Inside it, the actors/agents use strategy and capital, giving rise to a dominance dynamic, or intersection, and the dialectical relationship between the actor/agent and structure. Power also has resulted in new knowledge for each actor.